Prevalence of methicillin-resistant staphylococcus aureus and extended spectrum β–lactamase producers among bacteria isolated from infected wounds in a tertiary hospital in Ibadan city (2016)
Wound colonization by microorganisms is most frequently polymicrobial and incidences of high level resistance among bacterial isolates from wounds have been reported. Methicillin-resistant Staphylococcus aureus (MRSA) and extendedspectrum beta-lactamase (ESBL) producing Gram-negative bacteria both constitute serious challenge to physician in their choice of antibiotic treatment of infections caused by these bacteria. This study determined the antibiotic susceptibility profiles and prevalence of MRSA and ESBL producers among wound bacterial isolates from a tertiary hospital in Ibadan City. Forty (40) clinical bacterial isolates from five wound sources were collected from the Microbiology unit of the University College Hospital (UCH), Ibadan and were authenticated with standard bacteriological techniques. Antibiotic susceptibility test was done by disc-diffusion method using 19 antibiotics belonging to 12 classes. MRSA strains were detected by their resistance to cefoxitin and/or oxacillin antibiotics. Presumptive ESBL production was by double-disc synergy test using 30 μg cefotaxime and ceftazidime around 20/10 μg amoxicillin-clavulanic acid discs. ESBL confirmation was by minimum inhibitory concentration (MIC) using agar-dilution method. The authenticated isolates include Proteus spp (47.5%), Staphylococcus aureus (27.5%), Pseudomonas aeruginosa (12.5%), Klebsiella spp (7.5%), Acinetobacter baumanii (2.5%) and E. coli (2.5%). Distribution of the isolates collected according to wound sources includes: acute soft tissue wounds (35%), leg ulcer (32.5%), surgical wounds (17.5%), burn wounds (12.5%) and diabetic foot ulcer (2.5%). Distributions according to patients’ gender are: male (65%), female (35%), and according to age-groups are: 0 – 19 years (22.5%), 20 – 39 years (35%), 40 – 59 years (32.5%) and ≥ 60 years (10%). All (100%) the isolates were multidrug resistant (MDR) being resistant to ≥ 3 classes of antibiotics. Percentages of isolates resistance to each of the antibiotic include: piperacillin, piperacillin-tozobactam and amoxicillin-clavulanic acid were 100%, ceftazidime, cefuroxime, cefixime, aztreonam, sulphamethoxazole-trimethoprim, erythromycin, chloramphenicol and doxycyclin were > 70%, cefoxitin (62.5%), Nitrofurantion (52.5%), ciprofloxacin (45%), ofloxacin (35%), perfloxacin (37.5%), gentamicin (32.5%) and imipenem (2.5%). Of the 11 Staphylococcus aureus collected, 54.5% were detected to be MRSA strains while ESBL production was detected in 55.2% of the Gram negative isolates. This study revealed 100% MDR phenotype constituting high level of MRSA strains (54.5%) and ESBL producers (55.2%) among Gram-positive and Gram-negative bacterial wound isolates respectively. Hence, this calls for caution in the use of extended spectrum antibiotics in treating patients with infected wounds.